The burden of diabetes-related foot disorders in community-dwellers living in rural Ecuador: Results of the Atahualpa Project. (August 2016) - Del Brutto, Oscar H.; Mera, Robertino M.; King, Nathan R.; Zambrano, Mauricio; Sullivan, Lauren J.
Highlights: Prevalence of diabetes-related foot disorders is unknown in developing countries. Among diabetics in rural Ecuador, prevalence of these conditions is 67%. Only 20% of affected individuals had previous diagnosis by a physician. Most patients have moderate-to-severe risk for developing active diabetic foot disease. Abstract: Background/objectives: Prevalence of diabetes-related foot disorders (DRFD) in rural areas of developing countries is unknown. The burden of these conditions in Atahualpa, a rural Ecuadorian village, were assessed. Methods: Using a population-based design, Atahualpa residents aged ≥40 years with diabetes mellitus were identified. Ankle brachial index determinations were used to assess presence of peripheral arterial disease, and the Michigan Neuropathy Screening Instrument was used to estimate peripheral neuropathy. Ulcers in the foot/ankle as well as history of amputations were considered as evidence of active diabetic foot disease. Using a linear model of risk, factors that independently correlated with DRFD, were assessed. Results: Mean age of 110 participants was 64 ± 12 years (59% women). Peripheral arterial disease was diagnosed in 24% of cases and peripheral neuropathy in 59% (15% had both conditions). In the adjusted model, increasing age and being men increased the risk for DRFD. Active diabetic foot disease was noted in 7% of participants, and another 60% were at moderate-to-high risk for developing this complication (according to NHS Borders Foot Classification System). Conclusions: The prevalence of DRFD is high in rural Ecuador, and most of the affected individuals are at risk for developing active diabetic foot disease.